Assessment of freeware programs for the reconstruction of tomography datasets obtained with a monochromatic synchrotron‐based X‐ray source. (24th June 2015) - Wolkowski, Bailey; Snead, Elisabeth; Wesolowski, Michal; Singh, Jaswant; Pettitt, Murray; Chibbar, Rajni; Melli, Seyedali; Montgomery, James
<x xml:space="preserve">Abstract</x> Synchrotron‐based in‐line phase‐contrast computed tomography (PC‐CT) allows soft tissue to be imaged with sub‐gross resolution and has potential to be used as a diagnostic tool. The reconstruction and processing of in‐line PC‐CT datasets is a computationally demanding task; thus, an efficient and user‐friendly software program is desirable. Four freeware programs (NRecon, PITRE, H‐PITRE and Athabasca Recon) were compared for the availability of features such as dark‐ and flat‐field calibration, beam power normalization, ring artifact removal, and alignment tools for optimizing image quality. An in‐line PC‐CT projection dataset (3751 projections, 180° rotation, 10.13 mm × 0.54 mm) was collected from a formalin‐fixed canine prostate at the Biomedical Imaging and Therapy Bending Magnet (BMIT‐BM) beamline of the Canadian Light Source. This dataset was processed with each of the four software programs and usability of the program was evaluated. Efficiency was assessed by how each program maximized computer processing power during computation. Athabasca Recon had the least‐efficient memory usage, least user‐friendly interface, and lacked a ring artifact removal feature. NRecon, PITRE and H‐PITRE produced similar quality images, but the Athabasca Recon reconstruction suffered from the lack of a native ring remover algorithm. The 64‐bit version of NRecon uses GPU (graphics processor unit) memory for accelerated processing and is user‐friendly, but does not provide necessary parameters for in‐line PC‐CT data, such as dark‐field and flat‐field correction and beam power normalization. PITRE has many helpful features and tools, but lacks a comprehensive user manual and help section. H‐PITRE is a condensed version of PITRE and maximizes computer memory for efficiency. To conclude, NRecon has fewer imaging processing tools than PITRE and H‐PITRE, but is ideal for less experienced users due to a simple user interface. Based on the quality of reconstructed images, efficient use of computer memory and parameter availability, H‐PITRE was the preferred of the four programs compared.